Ecosystem Responses to Abrupt Climate Change: Teleconnections, Scale and the Hydrological Cycle - Higgins, Paul A. T.; Vellinga, Michael (Climatic change, 2004)
The occurrence of past and future abrupt climate change, such as could occur under thermohaline circulation (THC) weakening, is increasingly evident in the paleoclimate record and model experiments. We examine potential responses of ecosystem structure and function to abrupt climate change using temperature and precipitation patterns generated by HadCM3 in response to forced THC weakening. The large changes in potential ecosystem structure and function that occur are not focused in the North Atlantic region where temperature sensitivity to THC is highest but occur throughout the world in response to climate system teleconnections. Thus, THC weakening, which is often viewed as a European problem, has globally distributed ecosystem implications. Although temperature changes associated with THC weakening affect the extent of several high latitude biomes, the distribution of ecosystem change results primarily from changes in the hydrological cycle. Currently there remains large uncertainty in climate model projections of the hydrological cycle. Therefore, the predictions of the magnitude and location of ecosystem perturbations will also be characterized by large uncertainty, making impact assessment, and thus adaptation, more difficult. Finally, these results illustrate the importance of scale and disaggregation in assessing ecosystem responses. Small globally aggregated ecosystem responses to THC weakening, approximately five percent for NPP and biomass, mask large local and regional changes. [PUBLICATION ABSTRACT]